Risk of pulmonary fungal infections associated with biologics: a FAERS database disproportionality analysis - Li, Jing; Han, Zhi Wu; Gao, Shan Shan; Guo, Qie; Cang, Huai Qin (Frontiers in Immunology, 2025)
Objectivebiologics have significantly advanced the treatment of rheumatoid arthritis (RA) and psoriatic arthritis (PsA). However, real-world data regarding the risks of pulmonary fungal infections (PFI) associated with different biologics are limited. Our study aimed to explore PFI incidence among approved biologics, drawing on sources of real-world evidence.MethodsWe conducted a disproportionality analysis to evaluate the association between biologics and PFI using data from the Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) (2004–2024). We analyzed clinical features, co-occurring adverse events (AEs), time-to-onset (TTO).ResultsOur analysis included 3,695 patients who developed PFI following treatment with biologics. The study comprised 28.5% females, 28.6% males, and 42.9% with unspecified gender. The median age was 63 years (interquartile range [IQR] 52–71). Several biologics were associated with elevated PFI risk. Among them, the highest reporting odds ratio (ROR) were observed for infliximab(ROR = 26.02, 95% CI 17.72–38.21), rituximab(ROR = 16.23, 95% CI 13.06–20.18), tocilizumab(ROR = 14.45, 95% CI 12.28–17.00), and baricitinib(ROR = 11.01, 95% CI 7.77–15.59). Other biologics associated with a disproportionality signal in PFI risk included golimumab(ROR = 6.73, 95% CI 2.15-21.13), upadacitinib(ROR = 4.61, 95% CI 2.61–8.14), ustekinumab(ROR = 4.58, 95% CI 1.46–14.36), adalimumab(ROR = 3.45, 95% CI 2.08–5.72), tofacitinib(ROR = 3.18, 95% CI 2.04–4.95), abatacept(ROR = 3.16, 95% CI 1.74–5.73), etanercept(ROR = 2.58, 95% CI 2.06–3.24), certolizumab pegol(ROR = 1.64, 95% CI 1.27–2.10). The signal for secukinumab was not statistically (ROR = 1.70, 95% CI 0.55–5.32). Female was associated with an elevated risk of PFI and fatal outcomes in the logistic regression analysis. Tocilizumab and baricitinib showed a disproportionality signal for fatal outcomes. Our analysis suggested a trend of more pronounced PFI risk signals in elderly patients. TTO analysis demonstrated no significant gender-based differences. However, significant intergroup differences were observed between patients aged 45–64 years and those aged 65–74 years. Notably, TTO profiles varied substantially among biologics, ranging from 30 days (tocilizumab) to 393 days (etanercept).ConclusionOur findings suggest that concomitant use of biologics is associated with a stronger disproportionality signal for PFI. The inherent limitations and potential reporting biases of the FAERS database necessitate confirmation through large-scale, prospective clinical studies.